Pulmonary Mycobacterium marinum infection: 'fish tank granuloma' of the lung. Issue 4 (November 2016) - Velu, Prasad Palani; Fernandes, Susan E; Laurenson, Ian F; Noble, Donald D
A 65-year-old man presented with a six-month history of lethargy, weight loss and dry cough. He had a background of mild chronic obstructive pulmonary disease. Chest radiograph showed new right upper lobe cavitary opacification. Sputum cultures were acid-fast bacilli smear positive and yielded Mycobacterium marinum – a non-tuberculous mycobacterium (NTM) often found in aquatic environments and rarely associated with respiratory disease. The suspected source was silent aspiration of contaminated water, likely due to his initiating the siphon of his fish-tank by mouth. He completed a one-year course of rifampicin, ethambutol and clarithromycin, with negative repeat sputum mycobacteria cultures and radiological improvement. This case report demonstrates a successful approach to investigation and further management of Mycobacterium marinum pulmonary disease – a rare condition, particularly in immunocompetent individuals, with limited treatment guidelines.